Transformation of Local Print Media in the Era of Disruption to Maintain Business Continuity - Avian Yuliar Pranantha; Dadang Rahmat Hidayat; Teddy Kurnia Wirakusumah (PT Publikasiku Academic Solution, 2023)
This study aims to determine the transformation and convergence of local print media Harian Umum Lampung Post in the era of disruption to maintain its business continuity. In addition, it aims to find out the business strategy carried out in order to facilitate the dissemination of information in the digital era. The research was conducted using case studies and conducted with constructivist qualitative methodology. The subject of research or as an informant is a team of editors, including company leaders, selected based on purposive sampling techniques, which are included in nonprobability sampling techniques. Data collection techniques are carried out through observation (field observation), interviews and tracing documents related to the existence and business activities carried out by the Lampung Post General Daily. Data analysis is carried out by processing data, namely organizing data, sorting out data, synthesizing data, searching and finding what is important and deciding what will be conveyed in research. The results of this study show that Harian Umum Lampung Post has successfully implemented digitalization of media content production as a stage to expand information dissemination. Lampung Post General Daily also mediamorphoses into new media to make it easier for audiences to get news content. The convergence of media applied is also able to make companies more efficient and able to maintain business continuity so that business continues to be sustainable or sustainability in the midst of increasingly fierce media industry competition